(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the prevalence of Restless Legs Syndrome (RLS) and the effect of RLS on academic performance among medical school students. Material and Methods: Second and 3rd grade medical students were included in the study. A total of 171 students were asked to complete the questionnaires. Demographic data and sleep habits of the students were recorded. RLS was diagnosed according to the questionnaire results. The RLS severity and frequency are evaluated according to the International Restless Legs Syndrome Study Group (IRLSSG) Questionnaire results. Epworth Sleepiness Scale (ESS) scores were also noted. Results: RLS was found in 17 (9.9%) of the students. Thirteen of the students with RLS were female (76.5%). The median grade point average (GPA) of students who had RLS (CC [60-64]) was significantly lower than those of other students (BB [70-79]) (p = 0.02). There was no statistically significant difference between the disease severity and GPA of the students with RLS (p = 0.516). The median GPA scores were lower in patients with a higher frequency of complaints (p = 0.045). When the GPA of students with RLS were compared in terms of the of the ESS scores, the median GPA of the students who had excessive daytime sleepiness was significantly lower (p = 0.038).Conclusion: The worse academic performance of the students with RLS was more related with frequency of RLS symptoms rather than severity of symptoms. The cognitive impairment underlying worse academic performance was probably due to insomnia-related chronic sleep deprivation secondary to RLS.